2002
DOI: 10.1091/mbc.01-09-0435
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-regulated Exocytosis/Endocytosis in Bladder Umbrella Cells

Abstract: The epithelium of the urinary bladder must maintain a highly impermeable barrier despite large variations in urine volume during bladder filling and voiding. To study how the epithelium accommodates these volume changes, we mounted bladder tissue in modified Ussing chambers and subjected the tissue to mechanical stretch. Stretching the tissue for 5 h resulted in a 50% increase in lumenal surface area (from approximately 2900 to 4300 microm(2)), exocytosis of a population of discoidal vesicles located in the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
258
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(276 citation statements)
references
References 56 publications
(80 reference statements)
15
258
0
3
Order By: Relevance
“…Urothelium is a source of ATP release [28,50,51] and it is also an important site of adenosine biosynthesis. Importantly, both ATP and adenosine have functions in exocytosis of umbrella cell layer [52,53], which is the mechanism to increase the luminal surface area when the bladder fills (cytoplasmatic discoidal/fusiform vesicles fuse with the apical plasma membrane) [54]. The ATP released by urothelium is responsible for micturition reflex, through P2X3 from subepithelial nerve fibers [55].…”
Section: Discussionmentioning
confidence: 99%
“…Urothelium is a source of ATP release [28,50,51] and it is also an important site of adenosine biosynthesis. Importantly, both ATP and adenosine have functions in exocytosis of umbrella cell layer [52,53], which is the mechanism to increase the luminal surface area when the bladder fills (cytoplasmatic discoidal/fusiform vesicles fuse with the apical plasma membrane) [54]. The ATP released by urothelium is responsible for micturition reflex, through P2X3 from subepithelial nerve fibers [55].…”
Section: Discussionmentioning
confidence: 99%
“…The outermost layer of this tissue is lined by a single layer of polarized umbrella cells, which are known to respond to mechanical stimuli by augmented ion transport and membrane traffic (Lewis and de Moura, 1982;Truschel et al, 2002;Wang et al, 2003b); however, the relationship of these two processes and the mechanical force (stretch and/or pressure) that acts upon the umbrella cell to stimulate these events is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent "late" stage, which occurs after the tissue has reached a mechanical equilibrium, the surface area increases slowly over several hours (Balestreire and Apodaca, 2007). The late stage is temperature sensitive and is dependent on purinergic signaling pathways, activation of the EGF receptor, and protein synthesis and secretion (Truschel et al, 2002;Wang et al, 2003aWang et al, , 2005Balestreire and Apodaca, 2007). In contrast, the early stage is largely unexplored but appears to be insensitive to temperature and does not require EGF signaling or protein synthesis (Balestreire and Apodaca, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by chemical crosslinking and in vitro transfection analyses, the four major UPs form two distinct pairs (UPIa with II and UPIb with IIIa), in order for them to exit efficiently from the endoplasmic reticulum during biosynthesis (16,17). Because UPs are highly conserved during mammalian evolution (12), it has been suggested that they play key roles in urothelial functions, including participation in the permeability barrier, adjustment of urothelial surface area, stabilization of the urothelial surface and development of the urinary tract (12,18,19). Consistent with their proposed functions at the urothelial surface, UPs are expressed in a tightly differentiation-dependent manner, being detected ultrastructurally (in the form of AUMs) and immunohistochemically at the apical surface and cytoplasm of the superficial cell layer of human urothelium with little or no detection in the intermediate and basal layers (20,21).…”
Section: Introductionmentioning
confidence: 99%